The Impact of Socio-demographic Factors on the Recovery Potential of Schizophrenia Patients Post Hospitalization - Sri Mulyani (Masters Program in Public Health, 2024)
Background: Mental health is a series of emotional, psychological, and social well-being. Psychological well-being focuses on individuals having meaning in life and having choices in actualizing their potential. This study aimed to analyze the influence of socio-demographic factors on the recovery ability of schizophrenia patients after hospitalization.Subjects and Method: This research was conducted using a cross-sectional design carried out at the Outpatient Polyclinic of RSJD Dr. Arif Zainudin Surakarta from December 2023 to January 2024. The sample used in this study was 200 schizophrenia patients who were selected using purposive sampling. The independent variables in this study are gender, age, duration of illness, duration of hospitalization, education level, and employment status. The dependent variable is the recovery ability of schizophrenia patients after hospitalization. Data collection was carried out using a questionnaire and data was analyzed using a multiple linear regression analysis model.Results: The ability to recover from schizophrenia patients after hospitalization increased with female (b= 5.58; 95% CI= 1.29 to 9.87; p= 0.011), age ≥ 39 years (b= 0.66; 95% CI= -3.51 to 4.83; p= 0.756), high education (b= 7.24; 95% CI= 2.83 to 11.64; p= 0.001), and employed (b= 16.36; 95% CI= 12.06 to 20.67; p< 0.001). It decreased with a duration of illness ≥8 years (b= -5.77; 95% CI= -10.15 to -1.40; p= 0.010) and length of hospital stay ≥21 days (b= -6.88; 95% CI= -11.27 to -2.49; p= 0.002).Conclusion: The recovery ability of schizophrenia patients after hospitalization will increase with female, age ≥39 years, high education, and employed. It decreased with length of illness ≥8 years and length of stay ≥21 days.